Gerakan Identitas Minoritas Masyarakat Ras Papua: Studi Netnografi Gerakan #Papuanlivesmatter - Hilda Indah Bahirah; Agrenisa Pratiwi; Andini Lutfiah Putri; Restu Syahnanda (Sapientia Humana: Jurnal Sosial Humaniora, 2022)
Indonesia as it is known is an archipelagic country with various types of tribes, religions, races, regional languages, and cultures that develop in it. The diversity of tribes and various communities raises the problem of racism which is increasingly clouded by the rapid development of information and communication technology. The issue of racism, which is often carried out through social media, has in fact made the mass media open their voices and even more so the media and the community have also encouraged the government to be firm in giving moral and legal sanctions to anyone who commits racism. This study focuses on cases of racism that have long been felt by the Papuan people, which gave rise to the #PapuanLivesMatter movement. Because racial discrimination and racism against indigenous Papuans are still an important urgency which is a source of conflict in tolerance for diversity. So there needs to be synergy from various parties to stop this discriminatory practice. This study uses a netnographic method and data collection is carried out through online observations through hashtags on social media namely Instagram and Twitter as well as library data. This research has results including providing an overview of the uploaded content, namely the selection of visual use in photo, design, or video formats, how to convey messages (captions), and the involvement of activists who take part in the #PapuanLivesMatter Movement action. This study aims to explain that the #PapuanLivesMatter Movement demands justice and equality. THere is still a lot of discrimination and racism accepted by the Papuan.